2020
DOI: 10.1002/ps.5886
|View full text |Cite
|
Sign up to set email alerts
|

Double infection of Wolbachia and Spiroplasma alters induced plant defense and spider mite fecundity

Abstract: BACKGROUNDHerbivore‐associated bacterial symbionts can change plant physiology and influence herbivore fitness. The spider mite Tetranychus truncatus is a notorious pest harboring various bacterial symbionts; however, the effect of bacterial symbionts on host plant physiology remains unclear. Here, we investigated whether infection with the endosymbionts Wolbachia and Spiroplasma altered spider mite performance on tomato plants and affected plant‐induced defenses.RESULTSWolbachia and Spiroplasma were mainly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
(153 reference statements)
0
7
0
Order By: Relevance
“…Remarkably, the dominant microbe in the gut of D. simulans was Wolbachia, a common symbiont in insects and other arthropods and well known for manipulating host reproduction via various phenotypic effects [74,75]. Previous studies have also shown that Wolbachia could affect host immunity [9,10], influence host environmental adaptation [12,76], alter host-plant interactions [77,78], and influence other ecological and physical functions [3,4]. Some strains of Wolbachia have also been suggested to mediate reproduction, fitness, and immune responses in simulans [79][80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the dominant microbe in the gut of D. simulans was Wolbachia, a common symbiont in insects and other arthropods and well known for manipulating host reproduction via various phenotypic effects [74,75]. Previous studies have also shown that Wolbachia could affect host immunity [9,10], influence host environmental adaptation [12,76], alter host-plant interactions [77,78], and influence other ecological and physical functions [3,4]. Some strains of Wolbachia have also been suggested to mediate reproduction, fitness, and immune responses in simulans [79][80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Potato is reported as a host plant of several species of mites (Migeon 2015, Marić et al 2018, Migeon and Dorkeld 2022). Spider mites (Acari: Tetranychidae) are amongst the most damaging phytophagous pest families, currently encompassing 1,321 valid species that feed on 3,917 different plants, with approximately 0.9 billion Euros managing them every year (Zhu et al 2020, Migeon and Dorkeld 2022). In the early 1980s, Tetranychus truncatus Ehara, Tetranychus urticae Koch, and Tetranychus kanzawai Kishida were the three most devastating mites in China (Zhang et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…15 In the spider mite (Tetranychus truncatus), double infection of Wolbachia and Spiroplasma improved host reproductive performance and suppressed plant JA-and salicylic acid (SA)-responsive defence genes. 16 Therefore, the effects of Wolbachia on host biology are strain-and hostspecific. 17 Additional studies are needed to unravel the conserved and divergent mechanisms in arthropod-Wolbachia interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study showed that Wolbachia in D. virgifera virgifera was not able to suppress maize defence responses 15 . In the spider mite ( Tetranychus truncatus ), double infection of Wolbachia and Spiroplasma improved host reproductive performance and suppressed plant JA‐ and salicylic acid (SA)‐responsive defence genes 16 . Therefore, the effects of Wolbachia on host biology are strain‐ and host‐specific 17 .…”
Section: Introductionmentioning
confidence: 99%